Carl Schmitt’s Revenge—the Context of a Newly Discovered Publication by Schmitt - Hubertus Buchstein (Redescriptions)
The recent discovery of yet another (small) publication by Schmitt is more than just an interesting fact by itself for ardent Schmitt scholars. Including previously unknown archival material, the discovery sheds new light on three contexts of Schmitt’s relationship to his former favorite student Otto Kirchheimer: First, on the break-up of their personal contact as a consequence of George Schwab’s failed attempt to receive a PhD grade at Columbia University for his study on Schmitt in 1961; second, on the hidden connections between Schmitt’s and Kirchheimer’s concepts of political justice; and third, on Kirchheimer’s previously unknown contribution to Hannah Arendt’s book Eichmann in Jerusalem.